THE IMPACT OF TASK-BASED LANGUAGE TEACHING ON LEARNERS' WRITING SKILLS - Luz Elena Madera González; Margarita María López Pinzón (Universitas Kuningan, 2019)
This article gives an account of an action research project aimed at determining the effect of Task-Based Language Teaching and various writing strategies on public school learners' writing skills. The study implicated a diagnostic stage, an action stage and an evaluation stage within an Action Research methodology. Initially, at the diagnostic stage, it was detected that the participants had to improve their writing production and reach the levels of competence established by the Common European Framework (CEFR) and The Ministry of National Education (MEN) guidelines. In the following developed phase, six workshops were designed within the framework for Task-Based Learning (Willis & Willis, 2007), including pre-task, task, planning, report, and language focus. Along with this, various writing strategies were used, including brainstorming, listing, questioning, reading pictures, and classifying words. Finally, the evaluation stage revealed that students achieved better results in written production; they increased their vocabulary, reduced the amount of grammar errors, improved the syntax of the language, and became more autonomous and responsible. Basides, students' confidence in the writing processes also improved. Findings reported that the use of TBLT improved the students' writing skills. Conclusions and pedagogical implications are presented for teachers, schools and policy makers to incorporate TBLT and writing strategies in the future curriculum development as a means to contribute to the English language methodology.